Profile of non-compliance in lymphoblastic leukaemia. Issue 4 (1st April 1997) - Lancaster, D; Lennard, L; Lilleyman, J S
Abstract : A nationwide study of intracellular drug metabolite concentrations in children prescribed 6-mercaptopurine for the treatment of lymphoblastic leukaemia was carried out to assess interpatient variability at a standardised dose. Nine children (2% of the total) had completely undetectable metabolites, indicative of non-compliance. Five were adolescents, but otherwise they had no obvious distinguishing characteristics. Not taking any 6-mercaptopurine at all is uncommon, but the problem cannot be predicted. The total number of children who do not comply cannot be determined from this study, but the nine children described represent only a fraction of these.